Carcino-embryonic antigen may function as a chemo-attractant in colorectal-carcinoma cell lines. - Kim, J; Koo, K; Kim, B; Park, K; Bicknell, D; Bodmer, W (1999)
Locomotion of colorectal-carcinoma cells was tested in order to establish whether it might be affected by carcino-embryonic antigen (CEA). CEA production, cell growth and DNA ploidy were measured in 22 colorectal-carcinoma cell lines. A cell-invasion assay was adapted using a transfilter chamber, the lower surface of which was coated with various substrates in the amount of 5 microgram/filter (CEA, type-IV collagen, laminin). Cells infiltrated into the lower surface of the filter were counted over 9-microscope fields (x400). All cell lines produced CEA, 9 producing more than 100 ng/ml medium. Of the total, 8 cell lines were diploid and 14 were aneuploid. Invasiveness, measured by the number of infiltrated cells, was highest in CEA-coated filters, and next highest in type-IV-collagen- and laminin-coated filters, in descending order (p < 0.001-0.05). Invasiveness of each cell line was closely correlated with 2 substrates. Poorly differentiated or advanced-stage tumors were more invasive than well-differentiated or early-stage tumors (p < 0.001-0. 05). However, invasiveness was not associated with DNA ploidy or CEA production. CEA may function as a chemo-attractant as well as an adhesion molecule in colorectal-carcinoma cell lines. In addition, adhesion to CEA appears to be related to type-IV collagen and laminin.